Analisis Nutrisi Kerupuk Singkong (Manihot esculenta) dengan Fortifikasi Ikan Layang (Decapterus sp) - Karim, Mutemainna; Saokani, Jawiana; Reski, Reski (Jurnal Riset Diwa Bahari (JRDB), 2024)
This research aims to determine the effect of fortification of flying fish (Decapterus sp) on the nutritional value and best formulation of cassava crackers (Manihot esculenta). The benefits of this research are expected to provide information to the public about the most appropriate fortification of flying fish for the quality of cassava crackers based on the chemical properties of water content, ash content, protein content, fat, and crude fiber. This research was conducted in July-August 2022. Proximate testing was carried out at the Fishery Product Quality Implementation Center (BPMPP) and the Makassar Health Laboratory Center (BBLKM). The research method used was an experimental research method using an experimental design, namely a Completely Randomized Design (CRD) consisting of 4 treatments. Based on the ANOVA test, the research results showed that fortification of flying fish (Decapterus sp) had a significant effect on protein content, fat content, water content, ash content, and crude fiber content of cassava crackers (Manihot esculenta). Based on further tests using the Tukey test, it was found that the best formulation for fortification of flying fish (Decapterus sp) on cassava crackers (Manihot esculenta) was the formulation for sample D.